2017
DOI: 10.1038/s41598-017-17224-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and thermal properties of mineral-supported polyethylene glycol as form-stable composite phase change materials (CPCMs) used in asphalt pavements

Abstract: Three kinds of mineral-supported polyethylene glycol (PEG) as form-stable composite phase change materials (CPCMs) were prepared to choose the most suitable CPCMs in asphalt pavements for the problems of asphalt pavements rutting diseases and urban heat islands. The microstructure and chemical structure of CPCMs were characterized by SEM, FT-IR and XRD. Thermal properties of the CPCMs were determined by TG and DSC. The maximum PEG absorption of diatomite (DI), expanded perlite (EP) and expanded vermiculite (EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 28 publications
(21 reference statements)
2
20
0
Order By: Relevance
“…[5][6][7][8][9][10] In recent years, PCMs have been also applied in bitumen mixtures to enhance the temperature adaptability, which helps reduce the temperature damage of bitumen and extend the service life of bitumen pavement. 2,[11][12][13] Due to the unique features including suitable phase change temperatures, sufficient phase change latent heat, good phase change cycle stability and certain high temperature resistant properties, polyethylene glycol (PEG) has received considerable attention for application as a PCM. [14][15][16] However, the commercial application of PEG mainly faces two problems: low thermal conductivity and phase instability in melting state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] In recent years, PCMs have been also applied in bitumen mixtures to enhance the temperature adaptability, which helps reduce the temperature damage of bitumen and extend the service life of bitumen pavement. 2,[11][12][13] Due to the unique features including suitable phase change temperatures, sufficient phase change latent heat, good phase change cycle stability and certain high temperature resistant properties, polyethylene glycol (PEG) has received considerable attention for application as a PCM. [14][15][16] However, the commercial application of PEG mainly faces two problems: low thermal conductivity and phase instability in melting state.…”
Section: Introductionmentioning
confidence: 99%
“…3 The direct incorporation of PEG in bitumen may increase the saturated content of bitumen, which will reduce the consistency of bitumen, resulting in higher penetration and lower ductility. 11 PEG-based form-stable PCMs which are oen composed of PEG and supporting materials have been developed to overcome the shortcomings. These PEG-based form-stable PCMs such as PEG/ silica, [17][18][19][20] PEG/diatomite, 21,22 PEG/gypsum, 23 PEG/montmorillonite, 24,25 PEG/porous carbons, [26][27][28] and PEG/polymers, [29][30][31][32] can keep the solid state even when PEG is undergoing solid-liquid phase transition above the melting temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…36 Previous researchers have studied mixing PCM into bitumen to change the thermo-physical characteristic of bitumen pavement using the latent thermal characteristic and temperature control function of PCM. 26 It has been found that aged bitumen led to the premature deterioration of pavement structure. 37 For improving the applicability of PCM in building materials and bitumen pavements, we propose a promising PCMs (the PEG/ surface-modied LDHs) to provide thermal regulation and improve aging resistance resulting in improved durability and extended service life.…”
Section: + (Oh) 2 ]mentioning
confidence: 99%
“…The former group includes PEGnatural polymers, 15,16 PEG-acrylic polymers, 17 PEG-porous carbon materials (expanded graphite, activated carbon), [18][19][20] and PEG-hybrid organic systems. 21 The latter group is composed of PEG segments combining with different inorganic matter, such as silica, 3,4,7-9 montmorillonite, 22,23 diatomite, [24][25][26] gypsum and clays.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the montmorillonite can be combined with the nano-materials to allow the nanoparticles to enter into the montmorillonite layer to form a pillared modified montmorillonite. This method is conducive to enlarging the interlayer spacing of montmorillonite, forming an exfoliated structure in the organic polymer materials, increasing the surface area of the materials and improving the catalytic performance and interlayer cation exchangeability of the materials [15,16].…”
Section: Introductionmentioning
confidence: 99%